2018
DOI: 10.1038/s41559-018-0694-0
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic evidence for oligotrophication of terrestrial ecosystems

Abstract: Human societies depend on an Earth System that operates within a constrained range of nutrient 68 availability, yet the recent trajectory of terrestrial nitrogen (N) availability is uncertain. 69 Examining patterns of foliar N concentrations ([N]) and isotope ratios (δ 15 N) from more than 42,000 samples acquired over years, here we show that foliar [N] declined by 8% and foliar δ 15 N declined by 0.8 -1.9 ‰. Examining patterns across different climate spaces, foliar δ 15 N declined across the entire range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
167
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 172 publications
(204 citation statements)
references
References 212 publications
14
167
8
Order By: Relevance
“…Systematic investigation and collaborative analysis of the C:N ratio among different plant organs can reveal the adaptation strategies of the a plant continuum, which means that a plant is made up interrelated organs (Zhang, He, et al, ). Although the TRY plant trait database (https://www.try-db.org) provides a huge number of records of plant elements, it is more suitable for analyzing the characteristics of a single plant organ (Butler et al, ; Craine et al, ). In this study, we systematically examined variation in the C:N ratio of different organs across taxa and forest types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic investigation and collaborative analysis of the C:N ratio among different plant organs can reveal the adaptation strategies of the a plant continuum, which means that a plant is made up interrelated organs (Zhang, He, et al, ). Although the TRY plant trait database (https://www.try-db.org) provides a huge number of records of plant elements, it is more suitable for analyzing the characteristics of a single plant organ (Butler et al, ; Craine et al, ). In this study, we systematically examined variation in the C:N ratio of different organs across taxa and forest types.…”
Section: Discussionmentioning
confidence: 99%
“…Plant C:N ratio also differs among environments. N is considered as the most limiting element in terrestrial ecosystems (Craine et al, 2018). The degree of N limitation varies from region to region (LeBauer & Treseder, 2008) because of topography, climate, and nutrient supply (Chadwick, Derry, Vitousek, Huebert, & Hedin, 1999).…”
mentioning
confidence: 99%
“…Indeed, many terrestrial ecosystems are facing N limitation due in part to warming temperatures and declining N availability relative to increasing atmospheric concentrations of carbon dioxide (Craine et al . ). However, the importance of the urban N cycle is gaining recognition, given that an increasing majority of people live in cities (UN ) and the water they drink and air they breathe directly affect their health (Kampa and Castanas ; Schwarzenbach et al .…”
mentioning
confidence: 97%
“…Most research on atmospheric N deposition has been conducted in rural areas and has demonstrated declining deposition rates in places like the northeastern US, Europe, and the central Indo-Pacific (Ackerman et al 2018). Indeed, many ter-restrial ecosystems are facing N limitation due in part to warming temperatures and declining N availability relative to increasing atmospheric concentrations of carbon dioxide (Craine et al 2018). However, the importance of the urban N cycle is gaining recognition, given that an increasing majority of people live in cities (UN 2015) and the water they drink and air they breathe directly affect their health (Kampa and Castanas 2008;Schwarzenbach et al 2010).…”
mentioning
confidence: 99%
“…There is also evidence of increased C flow to soils increasing soil C availability and potentially stimulating microbial N immobilization in temperate forests (Groffman et al, 2018). The increased biological N uptake, combined with reduced atmospheric N inputs, have reduced the available N in soils, and there is accumulating evidence for the oligotrophication of these temperate forests (McLauchlan et al, 2017; Craine et al, 2018; Groffman et al, 2018). The results reported here also suggest that these forests may be transitioning to greater N limitation over time, and long‐term studies like BBWM are essential to understand how these changes are altering forest productivity and forest health.…”
Section: Discussionmentioning
confidence: 99%